IMPROVING STRATEGIES FOR PREVENTING UNEVEN SOCIO-ECONOMIC DEVELOPMENT OF AREAS (E Conference Zone, 2022)
The article discusses the need to improve strategies to prevent uneven socio-economic development of the regions. It calls for decentralization reform to address inequalities between regions, balanced development, and the coordination of sectoral reforms and the implementation of these policies by the regions and the local community in order to eliminate uneven development between regions.